Neddylation Inhibition Causes Impaired Mouse Embryo Quality and Blastocyst Hatching Failure Through Elevated Oxidative Stress and Reduced IL-1β - Yang, Guangping; Chen, Jianhua; He, Yanni; Luo, Hui; Yuan, Hongxia; Chen, Liangliang; Huang, Lingli; Mao, Fei; Hu, Saifei; Qian, Yun; Miao, Congxiu; Feng, Ruizhi (Frontiers in Immunology, 2022)
Mammalian blastocyst hatching is an essential prerequisite of successful embryo implantation. As the rate-limiting step of current assisted reproductive technology, understanding the key factors regulating blastocyst hatching would be significantly helpful to improve the performance of assisted reproductive practice. In early embryo development, the fine-tuned elimination of maternal materials and the balanced protein turnover are inevitable for the competent to hatch and implant into uterine endometrium. Neddylation, a ubiquitination-like protein modification, has been shown to involve in oocyte maturation and early embryo development. In this study, aiming to discover an unknown role of neddylation in blastocyst hatching process, we provided functional evidences of neddylation in mammalian embryo quality and blastocyst hatching. Treatment with MLN4924, a specific neddylation inhibitor lowered the embryo quality and dramatically reduced the hatching rate in mouse blastocysts. Transcriptional profile showed the upregulation of oxidative stress related genes and aberrant expression of immune-related genes. The elevated oxidative stress was validated by qPCR and markers of apoptosis, DNA damaging, reactive oxygen species and cytoskeleton. Moreover, we found the secreted IL-1β level was reduced in a NF-κB-independent manner, leading to the final poor embryo quality and blastocyst hatching failure. This is the first report of neddylation being of great importance in mammalian blastocyst hatching process. Further investigations uncovering more detailed molecular mechanisms of neddylation regulation in blastocyst hatching would greatly promote not only the understanding of this crucial biological process but also the clinical application in reproductive centers.